2022
DOI: 10.1161/circinterventions.121.011718
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural Pericardial Effusion Complicating Transcatheter Left Atrial Appendage Occlusion: A Report From the NCDR LAAO Registry

Abstract: Background : Pericardial effusion (PE) is a potential complication of transcatheter left atrial appendage occlusion (LAAO). The objective of this study was to investigate the incidence, associated characteristics, and outcomes of PE following LAAO. Methods : Patients in the NCDR LAAO Registry who underwent a Watchman procedure between January 1, 2016 and December 31, 2019 were included. The primary outcome was in-hospital PE requiring intervention (perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…The patient was discharged the following day. The pericardial effusion was attributed to the inherent procedural risk of left atrial instrumentation and LAAC device deployment 9 …”
Section: Resultsmentioning
confidence: 99%
“…The patient was discharged the following day. The pericardial effusion was attributed to the inherent procedural risk of left atrial instrumentation and LAAC device deployment 9 …”
Section: Resultsmentioning
confidence: 99%
“…The reported incidence of PE following Watchman implantation is relatively low. In a recent study from the NCDR Left Atrial Appendage Occlusion Registry, the incidence of PE requiring intervention was reported to be 1.4% ( 7 ). A real-world analysis of >17,000 recipients of the Watchman implant reported the incidence of PE requiring intervention to be 1.2% ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Amulet IDE trial, the incidence of postprocedural PE was reported to be higher for procedures in which the Amplatzer Amulet occluder was implanted than when the Watchman device was used ( 6 ). Several factors associated with PE after LAAC have been reported, including older age, female sex, left ventricular function, paroxysmal AF, and higher CHA 2 DS 2 -VASc score ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous left atrial appendage occlusion (LAAO) is an effective alternative for stroke prevention in patients with nonvalvular AF who cannot tolerate long‐term oral anticoagulation (OAC). Dual occlusive closure mechanism (disc and lobe type), Amulet device (Abbott; a second‐generation device that has replaced Amplatzer Cardiac Plug) was approved by the Food and Drug Administration (FDA) in August 2021 for percutaneous LAAO 1,2 . However, real‐world safety data on the delivery system (Amplatzer Cardiac Plug and Amplatzer Amulet device) are lacking.…”
Section: Figurementioning
confidence: 99%
“…Dual occlusive closure mechanism (disc and lobe type), Amulet device (Abbott; a second-generation device that has replaced Amplatzer Cardiac Plug) was approved by the Food and Drug Administration (FDA) in August 2021 for percutaneous LAAO. 1,2 However, real-world safety data on the delivery system (Amplatzer Cardiac Plug and Amplatzer Amulet device) are lacking.…”
mentioning
confidence: 99%